Семантична основа лексичної експресивності - Бойко, Надія; Boiko, Nadiia (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто основні типи лексичної експресивності: інгерентна (денотативно-конотативна, конотативно-денотативна, конотативна) та адгерентна (функціонально-семантична, функціонально-стилістична). На основі виділених типів лексичної експресивності здійснено розмежування мовної (семантичної) експресивності і мовленнєвої (функціональної), виявлено чотири класи експресивних лексичних одиниць: 1) експресиви з узуальними первинними значеннями; 2) експресиви з узуальними похідними значеннями; 3) експресиви з оказіональними (контекстуальними) значеннями; 4) слова зі стилістично зумовленим експресивним забарвленням. Встановлено роль і співвідношення денотації та конотації у структурі лексичного значення експресивного слова. In the article the two main types of lexical expressiveness are considered: inherent (denotative-connotative, connotative- denotative, connotative) and adherent (functional-semantic, functional-stylistic). The emphasisis is laid on the semantic basis of lexical expressiveness. The author distinguishes between language (semantic) expressiveness and speech (functional) expressiveness, and offers division of expressive lexical units into four basic classes: 1) expressive units with usual primary meaning (most frequently used); 2) expressive units with usual derivative meaning; 3) expressives with occasional contextual meaning; 4) words with stylistically stipulated expressive colouring. The article provides rich illustrative material to approve the role and coorilation of denotation and connotation in the structure of the expressive word lexical meaning. The article concludes that model of semantic structure of expressive words lexical meaning is represented by inherent expressive meaning, expressive colouring and expressive potential.
Semantic Basis of Lexical Expressiveness
Keywords: лексична експресивність; інгерентна експресивність; адгерентна експресивність; денотативний макрокомпонент; конотативний макрокомпонент; образний макрокомпонент; lexical expressiveness; expressivity gerente; adherent expressiveness; dentity macro component; connotative macro component; acro component of a figurative expression